Comprehensive Substrate-Based Exploration of Probiotics From Undistilled Traditional Fermented Alcoholic Beverage ‘Lugri’ - Baliyan, Neha; Dindhoria, Kiran; Kumar, Aman; Thakur, Aman; Kumar, Rakshak (Frontiers in Microbiology, 2021)
Cereal-based traditional fermented beverages (TFBs) are prevalent among India's ethnic community, and lugri is one such TFB popular among the tribal people of Lahaul valley in North-Western Himalaya. Previous studies have reported lugri to harbor probiotics and contain amino acids and vitamins. But, the comprehensive substrate-specific exploration of lugri for probiotic attributes was unexplored. The present study selected three substrate-based lugri (wheat, rice, and barley) to study their biochemical properties and explore potential probiotics. The best probiotic strains were screened for antioxidant studies and their fermentative process. The biochemical analysis determined that rice-based lugri had a higher content of alcohol content, electric conductivity, crude protein, and low pH than barley and wheat-based lugri. A total of 134 distinct morphotypes were screened, and 43 strains were selected based on their qualitatively superior acid and bile tolerance. Rice-based undistilled lugri harbored most probiotics as 22 out of 43 strains were isolated from it. All 43 bacterial isolates exhibited properties like cell surface hydrophobicity, cell-auto aggregation, β-galactosidase, and exopolysaccharide production, supporting them as possible probiotics. Based on antibiotic susceptibility, hemolytic activity, biofilm formation, all the bacterial strains were found to be non-pathogenic in nature. Taxonomically they ranged among eight distinct genera and 10 different species. Statistically, 12 isolates were found to be the most promising probiotic, and eight strains were isolated from rice-based undistilled lugri. Furthermore, the antioxidant activity of the promising isolates was tested based on free-radical scavenging ability towards 2,2-diphenyl-1-picrylhydrazyl (4.39-16.41%) and 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid (15.29-57.74%). The strain Lacticaseibacillus paracasei LUL:01 showed the best antioxidant activity and probiotic attributes, and hence was used for the production of fermented milk. The strain LUL:01 fermented the sterile milk within 18 hr, and the viable count remained above the legal requirement of 6 log10 CFU/ml during the 28 days storage at 4 °C. The strain has demonstrated the significant role of a suitable candidate for applying probiotic functional food formulation with several health benefits.